Ikramullah's fictional collection "The Jungle”: Critical Study - Muhammad Said Ali (دریافت)
Ikramullah's legendary collection "Jungle" has nine stories in total. The first four stories are based on realism, while the next four stories are symbolic and abstract. An allegorical drama is also part of the book. Human psychology, lust, social injustice, selfishness, poverty, compulsions, hunger, sex desire, virtual love, Man's tampering with nature, human instability are the main themes of these stories. These stories prove that Ikramullah's pen has immense potential for narrative, dialogue, observation, feelings, play of consciousness and subconscious, characterization and imagery. The beauty of all these short stories is that despite the symbolism and abstraction, the story is not lost. This article provides a critical overview of Ikramullah's fictional collection "Jungle".